Salutation and Role-Playing: Spiritual and Psychological Synergy to Strengthen the Confidence of Islamic Boarding School Student - Yusria Ningsih; Abdul Kadir Riyadi; Amalia Madihie (Prosperity: Journal of Society and Empowerment, 2024)
This study aims to investigate the effectiveness of combining sholawat therapy with role-playing techniques to enhance the self-confidence of santri at Darul Arqom Islamic Boarding School Surabaya. Santri, in this context, refers to students in Islamic boarding schools. A qualitative descriptive research method involves data collection through observation, interviews, and document analysis. The findings revealed that sholawat therapy with role-playing techniques had a significant positive impact on Santri's self-confidence. Santri, who participated in this program, experienced increased self-confidence, more active involvement in religious activities, and positive changes in their social behavior. This study suggests that sholawat therapy with role-playing techniques is an effective approach to strengthening Santri's self-confidence in the context of religious education. It provides a foundation for further developing this combination in clinical practice and religious education.